The effect of low-temperature straw-degrading microbes on winter wheat growth and soil improvement under straw return - Huang, Yuanyuan; Yan, Yuanyuan; Ma, Yang; Zhang, Xiang; Zhao, Qian; Men, Mingxin; Huang, Yali; Peng, Zhengping (Frontiers in Microbiology, 2024)
The application of straws degrading microbe with straw returned to field is an effective measure to improve soil quality, increase yield and maintain soil microorganisms. However, the utilization of straw-degrading microbes (SDM) in winter of north China is limited by the poor effects under low temperature. This study investigated the effects of a new compound SDM including a novel low-temperature fungi Pseudogymnoascus sp SDF-LT on winter wheat yield，soil improvement and soil microbial diversity. A two-year field experiment was conducted in two different soil textures of wheat-maize rotation fields with full corn straw return and application of SDM at the amount of 67.5 kg hm -2 . After two-years continuously application of SDM, the winter wheat yield increased significantly, reaching to 9419.40 kg hm -2 in Ningjin (NJSDM) and 9107.25 kg hm -2 in Mancheng (MCSDM), respectively. The soil properties have been significantly improved compared with single straw return group, especially the sandy loam soil whose quality is relatively low. Analysis of soil microbial diversity showed that SDM significantly reduced the Chao1, Shannon, Simpson and Observed species of the sandy loam soil in MCSDM group. The Simpson and Shannon indexes of fungi diversity in the two experimental sites were increased significantly by SDM. The negative correlation of fungi increased from 47.1% to 48.85% in the SDM groups. And the soil dominant microbes changed in SDM groups, in which the interactions between microbes were enhanced. These results suggest that SDM changed the community structure, and increased the soil microbial diversity and complexity, which is beneficial for crop growth. Our study provided sufficient evidence for the utilization of the low-temperature straw-degrading microbes with straw return in cold winter, which is function in soil improvement, especially for the low-quality soils, to increase crop yield.